Management of Acute Myeloblastic Leukemia in a Child With Biallelic Mismatch Repair Deficiency. Issue 8 (November 2015) - Elhasid, Ronit; Dvir, Rina; Rosenfeld Keidar, Hila; Ben Shachar, Shay; Bitan, Menachem; Solar, Irit; Durno, Carol; Aronson, Melyssa; Malkin, David; Hawkins, Cynthia; Bouffet, Eric; Tabori, Uri
Abstract : Germline biallelic mismatch repair deficiency (bMMRD) results in a unique cancer predisposition syndrome in which the affected children are susceptible to the development of malignancies, especially brain, gastrointestinal, and lymphoid cancers. Acute myeloblastic leukemia is rarely reported in this syndrome. Here we report the decision-making challenges in a bMMRD child with acute myeloblastic leukemia. Our experience should alert physicians to include bMMRD in the differential diagnosis of a child with hyper/hypopigmented spots and leukemia. Furthermore, the presence of the above and consanguinity emphasizes the need to rule out bMMRD when an allogeneic bone marrow transplant is considered and to enable the surveillance of other family members for earlier detection of cancers in these children.